Ake: The Years of Childhood - Soyinka, Wole (Spectrum Books Ltd, 1981)
The Nigerian playwright, poet, and novelist recounts his first eleven years growing up under the influence of his parents, traditional Yoruba customs, and Christian missionaries
Keywords: Biography & Autobiography; Non-Fiction / Biography - Wole Soyinka; Wole Soyinka